Diversity and habitat characteristics of gastropods and bivalves associated with mangroves on the east coast of Aceh Province, Indonesia - ABDUL L. MAWARDI; MUHAMMAD KHALIL; TRI MUSTIKA SARJANI; FAHMY ARMANDA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Mawardi AL, Khalil M, Sarjani TM, Armanda F. 2023. Diversity and habitat characteristics of gastropods and bivalves associated with mangroves on the east coast of Aceh Province, Indonesia. Biodiversitas 24: 5146-5154. Mangrove areas are vital for various gastropod and bivalve species as breeding, nursery, and stable nutrient supply grounds. This study aims to understand the habitat characteristics and diversity index of gastropods and bivalves and identify the associated species with mangrove vegetation along the east coast of Aceh Province, Indonesia. This research utilized a survey method with gastropod and bivalve sampling conducted using purposive sampling. Sampling was carried out at 6 research locations with varying environmental conditions. Gastropods and bivalves were collected from each research location using 1 m x 1 m plots. All collected gastropod and bivalve samples were preserved in a 4% formalin solution and later identified at the Biology Laboratory of Samudra University. A total of 5,293 individuals of gastropods and bivalves were found in the research locations, comprising 48 species and 21 families. The diversity index of gastropods and bivalves across all research locations showed a moderate criterion, indicating slight pollution on the east coast of Aceh Province. The highest diversity was observed at location 5, far from settlements and active fishing vessel activities. On the other hand, the lowest diversity was found at location 2, an area with active fishing vessel transportation to and from the fish auction site (TPI).